2019
DOI: 10.1063/1.5057389
|View full text |Cite
|
Sign up to set email alerts
|

CVD growth and properties of on-axis vanadium doped semi-insulating 4H-SiC epilayers

Abstract: Highly resistive homoepitaxial layers of 4H-SiC have been grown on the Si-face of nominally on-axis, n-type substrates using chemical vapor deposition (CVD). Vanadium tetrachloride has been used as V-dopant which is responsible for the high resistivity of the epilayers. 100% 4H-polytype was reproduced in the epilayers using optimized on-axis growth process and the upper limit of Vanadium tetrachloride flow rate for achieving defect-free high resistivity homoepitaxial layers was established. A resistivity of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…We examined a single-crystal 4H SiC sample with an homoepitaxial layer grown on an on-axis substrate [20]. The epilayer is 25 µm thick and was grown with vanadium tetrachloride as a source of V-dopant, leading to an inclusion density of 2 × 10 16 V/cm 3 as measured by SIMS.…”
Section: A Setup and Materialsmentioning
confidence: 99%
“…We examined a single-crystal 4H SiC sample with an homoepitaxial layer grown on an on-axis substrate [20]. The epilayer is 25 µm thick and was grown with vanadium tetrachloride as a source of V-dopant, leading to an inclusion density of 2 × 10 16 V/cm 3 as measured by SIMS.…”
Section: A Setup and Materialsmentioning
confidence: 99%
“…These dopants can act as donors (n‐type, electrons as the charge carriers, e.g., P, N 2 ), acceptors (p‐type, holes as the charge carriers, e.g., Al, B, Ga, Sc), or charge arrestors (e.g., V and Be) depending on the electronic configuration of each element. The presence of donors or acceptors decreases the electrical resistivity by providing charge carriers, while charge arrestors create deep levels within the bandgap and tend to increase the electrical resistivity by capturing the charge carriers 133,140 …”
Section: Factors Affecting Electrical Resistivity Of Porous Sic Ceramicsmentioning
confidence: 99%
“…Kultayeva et al 27 reported a difference of four orders of magnitude in the electrical resistivity of N 2 -doped (2.1 × 10 -1 Ω.cm) and undoped (1.2 × 10 3 Ω⋅cm) SiC at the same porosity of 62%. In addition to N 2 , 122-126 O 2 , 126,127 Al, [128][129][130][131] B, 131,132 V, 133,134 Be, 131 Ga, 122 Sc, 135,136 P, 123,124,137 C, 127 etc. are soluble in the SiC lattice.…”
Section: Doping Of Soluble Atomsmentioning
confidence: 99%
See 1 more Smart Citation
“…The p-i-n diodes were fabricated on a vertical stack of epilayers that was grown by CVD with the following structure: n + 4H-SiC substrate/semi-insulating (SI) layer (10 µm thick)/n − (17 µm thick). SI layer was grown through in-situ vanadium doping during growth using vanadium tetrachloride (VTC) in bubbler configuration 22 A high concentration of vanadium is known to produce extended defects in the epilayer. The flow rate of VTC was optimized to achieve defect free epilayer with SI properties (resistivity >10 5 cm).…”
mentioning
confidence: 99%